Speckle fields generated with binary diffusers and synthetic pupils implemented on a spatial light modulator - Cabezas Burbano, Luisa Fernanda (2015)
Digitally controllable Gaussian speckle fields were experimentally generated by implementing binary diffusers and synthetic pupils on a liquid crystal spatial light modulator. The synthetic pupil comprises a Ronchi phase mask and a proper filtering of its diffraction orders. The binary diffuser is displayed inside an aperture defined onto the Ronchi phase mask. We demonstrated that this implementation replaces the need of using a ground glass and a physical pupil. In this way, the average speckle size, the statistical independence among the generated speckle patterns, and the average intensity distribution can be dynamically controlled.